2019
DOI: 10.1037/fsh0000447
|View full text |Cite
|
Sign up to set email alerts
|

Implementation findings from an effectiveness-implementation trial of tablet-based parent training in pediatric primary care.

Abstract: The use of mobile delivery to deliver parent training can address barriers to access and improve the translation of interventions in existing settings like pediatric primary care. Studying implementation provides critical information to identify and address barriers and facilitators and inform sustainability efforts. Method: This study was a descriptive evaluation using the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework as part of a Hybrid Type I Effectiveness-Implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Meta-analyses indicate parenting internet- and mobile-based interventions (IMIs) can successfully reduce externalizing and internalizing difficulties in young people ( Nieuwboer et al, 2013 ; Spencer et al, 2020 ), with no significant difference in intervention effects found between online and face-to-face parenting programs ( Florean et al, 2020 ). Examples of preventive parenting IMIs targeting youth mental health include Cool Little Kids Online ( Morgan et al, 2016 ; Morgan et al, 2017 ), ez Parent ( Breitenstein et al, 2016 ; Breitenstein et al, 2019 ), Triple P Online ( Baker et al, 2017 ; Sanders, 1999 ; Sanders et al, 2003 ), Parenting Resilient Kids ( Fernando et al, 2018 ; Sim et al, 2020 ), ParentWorks ( Piotrowska et al, 2020 ), and Partners in Parenting ( Cardamone-Breen et al, 2018 ; Yap et al, 2018 ; Yap et al, 2019 ).…”
mentioning
confidence: 99%
“…Meta-analyses indicate parenting internet- and mobile-based interventions (IMIs) can successfully reduce externalizing and internalizing difficulties in young people ( Nieuwboer et al, 2013 ; Spencer et al, 2020 ), with no significant difference in intervention effects found between online and face-to-face parenting programs ( Florean et al, 2020 ). Examples of preventive parenting IMIs targeting youth mental health include Cool Little Kids Online ( Morgan et al, 2016 ; Morgan et al, 2017 ), ez Parent ( Breitenstein et al, 2016 ; Breitenstein et al, 2019 ), Triple P Online ( Baker et al, 2017 ; Sanders, 1999 ; Sanders et al, 2003 ), Parenting Resilient Kids ( Fernando et al, 2018 ; Sim et al, 2020 ), ParentWorks ( Piotrowska et al, 2020 ), and Partners in Parenting ( Cardamone-Breen et al, 2018 ; Yap et al, 2018 ; Yap et al, 2019 ).…”
mentioning
confidence: 99%
“…One notable line of research has been conducted on the ez Parent Program, which is a tablet-based preventive behavioral parent training intervention adapted from the Chicago Parent Program [ 43 ] tailored for youth aged 2 to 5 years in primary care settings. An advantage of the development strategy for ez Parent is that many of its aspects, including implementation factors, adherence, and parental perceptions of engaging with the program, have been studied [ 44 - 46 ]. Nevertheless, when tested in a randomized controlled trial, ez Parent was not more effective on child outcomes than enhanced usual care [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a Type I effectiveness-implementation trial of ez Parent at four primary care clinics (Breitenstein et al, 2019). The primary focus of a Type I effectiveness-implementation trial is intervention testing with a secondary focus on implementation factors (Landes, McBain, & Curran, 2019).…”
mentioning
confidence: 99%
“…We defined successful referrals as completion of three standardized steps: (1) provision of an information packet about the study, (2) a verbal conversation/referral from a PCP, and (3) documentation of the referral. After clinic personnel completed the ez Parent referral process, study personnel provided parents with information about the study and, if consented and enrolled, a tablet to access either ez Parent or the active control intervention (general child development resources; Breitenstein et al, 2019). Implementation outcomes from this study showed substantial variation among clinics in implementing referral protocols: average referral rates (the percentage of eligible parents who received referrals) were 14% (range = 7%–52%; Breitenstein et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation